2017
DOI: 10.1093/ecco-jcc/jjx080
|View full text |Cite
|
Sign up to set email alerts
|

Serial Tuberculosis Screening in Inflammatory Bowel Disease Patients Receiving Anti-TNFα Therapy

Abstract: Tuberculosis tests conversions were common in inflammatory bowel disease patients treated with infliximab alone or in association with immunomodulators. In these immunosuppressed individuals, the classical tuberculosis skin test seems to have a higher sensitivity than the modern tests based on the release of interferonϒ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 25 publications
0
29
0
Order By: Relevance
“…The development of active TB in patients under TNF-α antagonists might be main outcome to evaluate the efficacy of assay. However, only seventeen of our included studies [25,27,33,36] reported the follow-up data of patient and 74 active cases were reported [36]. The concordance between IGRAs and TST was poor to moderate which demonstrates the differences between these two tests.…”
Section: Studies Comparing Tst and Qft-git And Evaluating The Clinicamentioning
confidence: 87%
See 3 more Smart Citations
“…The development of active TB in patients under TNF-α antagonists might be main outcome to evaluate the efficacy of assay. However, only seventeen of our included studies [25,27,33,36] reported the follow-up data of patient and 74 active cases were reported [36]. The concordance between IGRAs and TST was poor to moderate which demonstrates the differences between these two tests.…”
Section: Studies Comparing Tst and Qft-git And Evaluating The Clinicamentioning
confidence: 87%
“…All these studies used both TST and QuantiFERON tests (10 QFT-GT and 17 QFT-GIT) before TNF-α inhibitor therapy. The ten of these papers evaluated both QFT and T-SPOT.TB or T-SPOT.TB [36][37][38][39][40][41][42][43][44][45].…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a lack of information and some controversy regarding the most effective latent TB rescreening method during anti-TNF therapy. In a recent Portuguese study about the utility and sensitivity of TB screening during anti-TNF therapy, TST appeared to be more sensitive than IGRA in the diagnosis of latent infection [21]. Additionally active TB must be ruled out in patients with persistent fever or clinical deterioration [7].…”
Section: Discussionmentioning
confidence: 99%